Disease progression in proposed brain-first and body-first Parkinson’s disease subtypes - Zhiheng Xu; Tianyu Hu; Chenqin Xu; Xiaoniu Liang; Shiyu Li; Yimin Sun; Fengtao Liu; Jian Wang; Yilin Tang (npj Parkinson's Disease, 2024)
Abstract A new Parkinson’s disease (PD) subtyping model has been recently proposed based on the initial location of α-synuclein inclusions, which divides PD patients into the brain-first subtype and the body-first subtype. Premotor RBD has proven to be a predictive marker of the body-first subtype. We found compared to PD patients without possible RBD (PDpRBD–, representing the brain-first subtype), PD patients with possible premotor RBD (PDpRBD+, representing the body-first subtype) had lower Movement Disorders Society Unified Parkinson’s Disease Rating Scale part III (MDS UPDRS-III) score (p = 0.022) at baseline but presented a faster progression rate (p = 0.009) in MDS UPDRS-III score longitudinally. The above finding indicates the body-first subtype exhibited a faster disease progression in motor impairments compared to the brain-first subtype and further validates the proposed subtyping model.